A study of factors that influence high unemployment rate among graduate: at Seberang Jaya / Siti Aishah Abd Mutalib - Abd Mutalib, Siti Aishah (2014)
Unemployment rate among graduates recently had increased its number for every year and become larger (Muk Ngiik and Jamil Hamali, 2011). This research is done to identify the factors that influence high unemployment among graduates. There are several factors that may influenced to high unemployment rate among graduates, but for this study, the researcher are provide only three factors which is lack of experience (Gurvinder and Sharan, 2008), lack of social and communication skills (Gurvinder and Sharan, 2008) and mismatch of courses (Muk Ngiik and Jamil Hamali, 2006). Due to the increasing reported by Department of statistic (Labour Force Statistics, Dec 2013), about the numbers of unemployed graduates, the researcher decided to choose this topic. Researcher have decided to choose Seberang Jaya as location to done her research which is located many SME’s organization, Banking, and Legal Firms which can give feedback to answer the questionnaires. The objective of this study is to identify the level of unemployment rate among graduate, to identify which factor is most significant to high unemployment rates toward graduates, and to examine the relationship between lack of experience, social and communication skills, and mismatch of courses to unemployment graduate. The data is collected through a questionnaire to 38 respondents by using purposive sampling. Result from the analysis showed that the significant relationship between factors of unemployment among graduate and high unemployment rate among graduate. This study also used regression analysis in order to identify which factors is most significant to high unemployment rate among graduate in Malaysia. Recommendations for future research are also having been discussed.